Presidential Address - Sustainable Management of diseases of sunflower - MAYEE, C.D. (Indian Phytopathology, 2002)
Management strategies for the control of sunflower diseases in India are discussed under the following headings: diseases in sustainable production systems; bridging technology transfer gaps; nonchemical disease management practices (cultural); host resistance; biological management strategies; chemical management strategies; integrated disease management; extension sunflower pathology; and bridging technology development gaps.